In Silico Study of Gingerol and Shogaol from Red Ginger Rhizome (Zingiber Officinale var. rubrum) as Anti-Inflamatory - Kumara Dewi, Ni Wayan Rika; Sukma Dinda, Ni Made Ayu; Suastini, Ni Made (Jurnal Skala Husada : The Journal of Health, 2025)
ABSTRACTInflammation occurs when the enzyme phospholipase A2 (PLA2) releases arachidonic acid from cell membranes, leading to the production of pro-inflammatory mediators. Gingerol and shogaol are bioactive compounds with anti-inflammatory properties found in red ginger (Zingiber Officinale var. rubrum). This research aims to investigate the potential anti-inflammatory activity of gingerol and shogaol against osteoarthritis using in silico methods. The in silico tests utilized Hyperchem 8, Chimera 1.10.1, and molecular docking was performed using AutoDock Tools, supplemented with Autogrid and Autodock 4. The results of molecular docking showed hydrogen bonds and binding energy. The binding energy values for 10-gingerol were -9.01 kcal/mol, 10-shogaol -8.85 kcal/mol, 8-shogaol -8.72 kcal/mol, and 6-gingerol -8.07 kcal/mol. The results indicate that gingerol and shogaol compounds have higher binding energies compared to the target protein Phospholipase A2 (Sodium Diclofenac) at -7.57 kcal/mol. This suggests that gingerol and shogaol compounds from red ginger rhizome (Zingiber Officinale var. rubrum) have potential as anti-inflammatory agents.Keywords:  gingerol; shogaol; anti-inflammatory; phospoliphase A2; in silicoABSTRAKInflamasi atau peradangan terjadi akibat enzim phospoliphase A2 (PLA2) yang melepaskan asam arakidonat dari membran sel, sehingga menghasilkan mediator proinflamasi. Gingerol dan shogaol merupakan senyawa bioaktif yang memiliki kandungan antiinflamasi pada tanaman jahe merah (Zingiber Officinale var. rubrum). Penelitian ini bertujuan untuk mengetahui potensi aktivitas dari gingerol dan shogaol sebagai antiinflamasi terhadap penyakit osteoartritis secara in silico. Uji in silico menggunakan program Hyperchem 8, Chimera 1.10.1 dan pengujian molecular docking menggunakan program  AutoDock Tools, dilengkapai dengan program (Autogrid dan Autodock 4). Hasil pengujian molecular docking adalah ikatan hidrogen dan energi ikatan. Nilai energi ikatan pada senyawa 10-gingerol sebesar -9,01 kkal/mol, 10-shogaol sebesar -8,85 kkal/mol, 8-shogaol sebesar -8,72 kkal/mol dan 6-gingerol sebesar -8,07 kkal/mol, Hasil menyatakan bahwa senyawa gingerol dan shogaol memiliki energi ikatan yang lebih besar dibandingkan dengan protein target Phospholiphase A2 (Natrium Diclofenac) sebesar -7,57 kkal/mol. Hal ini menunjukan bahwa senyawa gingerol dan shogaol dari Rimpang Jahe Merah (Zingiber Officinale var. rubrum) berpotensi sebagai antiinflamasi.Kata kunci:gingerol; shogaol; antiinflamasi; phospoliphase A2; in silico